Pembentukan Karakter Rendah Hati Peserta Didik Dalam Al-Qur’an Surah Al-Furqan 63-64 Kajian Ilmu Pendidikan Islam - Fauziah, Hapsah; Mahpudz, Sahal (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Education and character development are crucial aspects of an individual’s life, as character significantly influences one's success. Therefore, it is essential to cultivate strong and positive character traits continuously. One such important trait is humility, known in Islam as "tawadhu’". Tawadhu’ reflects a Muslim’s modesty and humility towards others. In contemporary society, particularly among students and teenagers, there is a prevalent tendency to follow the latest lifestyle trends. This trend has led to a decline in the youth's interest in positive activities and an increase in juvenile delinquency, especially within the educational sphere. Consequently, the implementation of character education, specifically the cultivation of humility, in both formal and informal educational settings, is deemed vital. It serves as a measure to counteract various social upheavals and moral decadence prevalent in society. This study aims to: (1) Understand the concept of Islamic Education; (2) Explore the development of students' humility as depicted in the Quran, Surah Al-Furqan, verses 63-64; (3) Examine the formation of humility in students in the context of Islamic Education through the analysis of Quran, Surah Al-Furqan, verses 63-64. This research employs a descriptive qualitative analytical method, utilizing a library research approach. Primary sources include the Quran (Surah Al-Furqan, verses 63-64), and secondary sources consist of tafsir (exegesis), books, and journals relevant to this study. Data collection techniques include documentation, qualitative analysis, and content analysis within the framework of Islamic Education Studies. The findings indicate that the formation of students' humility, as examined in Surah Al-Furqan, verses 63-64, involves three key aspects: First, students should consistently practice good behavior. Second, they should avoid despicable actions. Third, they must maintain a strong connection with Allah SWT by enhancing their religious devotion and obedience. Keywords: Humility, Islamic Education, Students